A new systemic model for the implementation of sustainable space science and technology investment for Sub-Saharan African economies: an implementation process derived from a case study of MeerKAT and the Square Kilometre Array projects - Mitchell, Carla (Department of Electrical Engineering, 2025)
This research develops a sustainable implementation model for African developing nations undertaking space science and technology (SST) programmes, using the MeerKAT project and the forthcoming Square Kilometre Array (SKA) as central case studies. Econometric analysis of Sub Saharan African (SSA) economies reveals that standard economic inputs namely labour, capital, and technology, are insufficient to plan for or predict growth in this context. Instead, a broader set of socio-economic variables, often overlooked in conventional models, must be considered. Panel data from 48 SSA countries informed the construction of four composite variables—access to finance, employment, education, and technology efficiency—which more accurately reflect the region's structural and cultural conditions. Findings indicate that SST investments have an inconsistent impact on labour productivity, largely due to inefficiencies in technology absorption and local capacity utilisation. In response, this research proposes a three-phase Space Science and Technology Framework (SSTIF) made up of the Impact Causality Cycle (ICC) which establishes causal links between SST investments and socio-economic outcomes, emphasising effective technology deployment. The Political Decision Matrix (PDM) which guides sustainability-oriented investment planning by evaluating socio economic benefits, as demonstrated through the MeerKAT project. A result of the PDM case study is that socio economic investment reduces project risk and improves sustainability. The Science-Driven Economic Benefit (SDEB) which model translates these insights into a practical implementation cycle, tested through a detailed application to the MeerKAT case. Together, these phases form an integrated pathway from theory to decision-making to implementation. The SKA project, as an expansion of MeerKAT, validates the framework's scalability and relevance, reinforcing the case for strategic SST investment in SSA. Ultimately, this thesis contributes a practical roadmap for policymakers—linking science infrastructure to inclusive economic development and long-term investment sustainability.